Perlaksanaan Perundangan Islam di Malaysia: Satu Penilaian - Yaacob, Abdul Monir (Jurnal Fiqh, 2009)
This article elaborates the implementation of Islamic law in Malaysia. It includes, inter alia, the British influence in the administration of Islamic law during colonial period, the status and jurisdiction of Shariah Courts before and after Malaysia achieved independence. The article also examines the codification of Islamic Law and the interpretation to article 121 (1A) of the Federal Constitution by the Civil Courts as to whether the Syariah Courts have exclusive jurisdiction in matters which the Shariah Courts have jurisdiction. It also deals with the issue of conversion and which court has jurisdiction on this matter. The objective of the article is to show that Islamic Law was the law of the land since the Malay Sultanate ruled Malacca. The British interference in the administration of Islamic justice has reduced its application to only personal matters. The position of Shariah Courts after the Court Ordinance 1948 came with effect. The purpose of article 121 (1A) of the Federal Constitution is to avoid conflict of jurisdiction between Civil Courts and Syariah Courts. The role of Shariah and Civil laws Technical Committee in drafting new laws for the Shariah Courts. From the overview of the development of Islamic Law in Malaysia there are other areas which need reforms. In the concluding part several recommendations were suggested for consideration.